Genomic study of a novel magnetotactic Alphaproteobacteria uncovers the multiple ancestry of magnetotaxis. (16th October 2018) - Monteil, Caroline L.; Perrière, Guy; Menguy, Nicolas; Ginet, Nicolas; Alonso, Béatrice; Waisbord, Nicolas; Cruveiller, Stéphane; Pignol, David; Lefèvre, Christopher T.
Summary: Ecological and evolutionary processes involved in magnetotactic bacteria (MTB) adaptation to their environment have been a matter of debate for many years. Ongoing efforts for their characterization are progressively contributing to understand these processes, including the genetic and molecular mechanisms responsible for biomineralization. Despite numerous culture‐independent MTB characterizations, essentially within the Proteobacteria phylum, only few species have been isolated in culture because of their complex growth conditions. Here, we report a newly cultivated magnetotactic, microaerophilic and chemoorganoheterotrophic bacterium isolated from the Mediterranean Sea in Marseille, France: Candidatus Terasakiella magnetica strain PR‐1 that belongs to an Alphaproteobacteria genus with no magnetotactic relative. By comparing the morphology and the whole genome shotgun sequence of this MTB with those of closer relatives, we brought further evidence that the apparent vertical ancestry of magnetosome genes suggested by previous studies within Alphaproteobacteria hides a more complex evolutionary history involving horizontal gene transfers and/or duplication events before and after the emergence of Magnetospirillum, Magnetovibrio and Magnetospira genera. A genome‐scale comparative genomics analysis identified several additional candidate functions and genes that could be specifically associated to MTB lifestyle in this class of bacteria.